Introduction: Shaping a Humane World (Comparative & International Education Series, 2022)
The book Humane World through Global Higher Education: Pre-Challenges and Post-Opportunities During a Pandemic responds to some of the conversations presented at the 2020 inaugural Virtual Star Scholar conference hosted by the University of Katmandu, Nepal. This conference aimed to bring together voices from worldwide to talk about what a Humane World will be in the post-COVID era. It is important to note that the meeting convened during the height of COVID-19, at a time hope was only a dream.How to cite this chapter:Valeau, E., & Raby, R. (2022). Introduction. In E. J. Valeau, R. L. Raby, & U. Gaulee (eds), Shaping a humane world through global higher education: Pre-challenges and post-opportunities during a pandemic (pp. 1-18). STAR Scholars.